2022
DOI: 10.3389/fendo.2022.1073592
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in cytologically indeterminate thyroid nodules harboring thyroid stimulating hormone receptor mutations

Abstract: ObjectivesTo evaluate the frequency and risk of malignancy of TSHRpI568T mutations discovered in indeterminate thyroid nodules (ITN) within the Veracyte CLIA laboratory undergoing Afirma® Genomic Sequencing Classifier (GSC) testing, and to evaluate a broader cohort of TSHR variants and their categorization as Afirma GSC benign (GSC-B) or suspicious (GSC-S). Finally, we seek to assess the risk of malignancy (ROM) of this group of TSHR mutated ITN in the GSC-S category.MethodsITN submitted to Veracyte for Afirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Recently, both original research and literature review have demonstrated that certain molecular variants lessen the ROM in GSC-S ITN samples from a standard ROM of 50% with a GSC-S result by the GSC ensemble classifier. For example, Whitmer et al 23 have reported Afirma will classify 95% of indeterminate thyroid nodules harboring thyroid stimulating hormone receptor (TSHR) variants as GSC-B, which represents an enhancement beyond solely reporting the presence or absence of these variants. In contrast, when the GSC ensemble classifier reports them as GSC-S, the risk of malignancy is ≥15%.…”
Section: Afirma Testing For Nodules With Biii and Biv Cytologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, both original research and literature review have demonstrated that certain molecular variants lessen the ROM in GSC-S ITN samples from a standard ROM of 50% with a GSC-S result by the GSC ensemble classifier. For example, Whitmer et al 23 have reported Afirma will classify 95% of indeterminate thyroid nodules harboring thyroid stimulating hormone receptor (TSHR) variants as GSC-B, which represents an enhancement beyond solely reporting the presence or absence of these variants. In contrast, when the GSC ensemble classifier reports them as GSC-S, the risk of malignancy is ≥15%.…”
Section: Afirma Testing For Nodules With Biii and Biv Cytologymentioning
confidence: 99%
“…In contrast, when the GSC ensemble classifier reports them as GSC-S, the risk of malignancy is ≥15%. 23,24 Such personalized and nuanced information may reassure clinicians and patients who prefer an active surveillance plan for ITN with a low (although not benign) molecular risk of malignancy. Given Afirma XA findings may alter clinical decisions beyond the GSC-B and GSC-S call, as well as the prognostic information that may be gleaned from the presence of specific molecular variants and fusions, the Afirma report automatically includes XA information for all GSC-S and, as will be described, nodules with BV and BVI cytology as of April 2023.…”
Section: Afirma Testing For Nodules With Biii and Biv Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…На сьогодні хвороба Грейвса (ХГ) розглядається як класичне автоімунне захворювання, в якому головну патогенетичну роль відіграють стимулюючі антитіла (АТ) до рецептора тиреотропного гормону (рТТГ), які здатні стимулювати ріст і функцію тиреоцитів [1]. Оскільки більшість вузлів щитоподібної залози (ЩЗ), включно зі злоякісними, зберігають експресію рТТГ [2,3], існує ймовірність того, що стимулюючий ефект може бути результатом зв'язування АТ з рТТГ вузлових утворень (ВУ). Цей процес може відбуватись у тиреоцитах, що мають соматичні генетичні/епігенетичні зміни, які спричиняють зростання ВУ.…”
unclassified